Manajemen Proyek Teknologi Informasi untuk Meningkatkan Pengetahuan PKK Desa Kalianan dengan Palatihan Menggunakan Marketplace - Syafiih, M; Maulana, Alfian Ilham; Hotija, Siti; Inda Arifin, Nur Hatima; Hati , Suci (Insan Kreasi Media, 2022)
Marketplace is a sales application that is freely accessible by all people, application providers selling between sellers and buyers do not have to meet face to face. Information Technology Project Management as management to manage in building projects. Kalianan Village, Krucil District, Probolinggo Regency, a village that has very good natural potential but is not matched by balanced Human Resources (SDA) so that good natural potential cannot be managed. The very basic problem is not balanced between the potential of nature and the potential of the people of Kalianan Village, Krucil District, Probolinggo Regency. Community service aims to provide knowledge capabilities in utilizing the results in the form of canna tubers as food raw materials. Provide knowledge in using marketplace applications so that people can sell entrepreneurial results into online sales applications. The result of this service is that the people of Kalianan Village, Krucil District, Regency have the ability to sell their wares online in the marketplace application